Pelatihan Pengolahan Hasil Perikanan Pada Ibu-Ibu Nelayan Kelurahan Pantai Amal - Alawiyah, Tuty; Gaffar, Syamsidar; Rachmawani, Dori; Irawati, Heni; Haryono, M. Gandri; Firdaus, Muhammad; Taqwa, Amrullah; Wiharyanto, Dhimas; Salim, Gazali; Roem, Muhammad; Jabarsyah, Abdul; Achyani, Ratno; Yushra, Yushra; Yusuf, Muhammad Yusfi; Romdoni, Taufiq Ahmad; Kase, Ardy Andreas Bernard; Muhtar, Dian Islamia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Partnership Program (PKM) aims to enhance the capacity of fisherwomen in Pantai Amal Village, Tarakan City, in processing fishery products into high-value economic commodities through educational-based training and outreach. The local community faces challenges in utilizing aquaculture products such as seaweed and milkfish, which are typically sold in raw form at low prices. This community service activity consists of several stages, including coordination with local leaders, collection of raw materials, dissemination of fish and seaweed nutritional information, and training in processing fishery products into seaweed dodol, amplang, and pempek. The results show that the training increased participants’ knowledge, skills, and creativity in diversifying fishery products. This service activity contributes to the development of educational science, particularly in community empowerment through nutritional literacy, household entrepreneurship, and contextual learning based on local potential. It is expected that this model of educational empowerment can be replicated in other coastal areas.